Assessing structure and dynamics of fibrinogen films on silicon nanofibers: Towards hemocompatibility devices - Hassan, Natalia (2012)
An enhanced knowledge of the interaction of proteins with the surfaces of implantable materials, particularly regarding fibrinogen (Fb), is fundamental for understanding cellular events and the overall host response. Thinking of future use of Si-nanofibers as three-dimensional (3D) scaffolds for construction of implantable artificial devices, the correlation among the material surface characteristics and the amount, structure and distribution of adsorbed Fb molecules are analyzed. The Fb adsorption process occurs in a stepwise fashion with an initial rapid adsorption, an intermediate reorganization and finally a second slower adsorption regime over a longer period of time. There is a partial desorption of the protein after the first adsorption process, which demonstrates that this step is reversible until 2 × 104 s. Nevertheless the whole process is irreversible, with a high distortion of the original material morphology. The limiting value for the adsorbed Fb surface concentration is about 270 ± 20 μg dm-2; more than three times the adsorption capacity of non fibrillar, 2D or 3D, scaffolds. The fibrous structure and the similitude in size between the substrate (d = 30-50 nm) and the Fb molecules (47-50 nm) are proposed to be the key to the enhanced adsorption process and the acquired final topography of the material.